Key performance indicators for excellent teachers in Malaysia: A measurement model for excellent teaching practices - Amzat, Ismail Hussein (Emerald Publishing Limited, 2017)
Purpose The purpose of this paper is to create a key performance indicator (KPI) that can be used as the benchmark tool for teaching performance and practices of both excellent teachers (ETs) and non-ETs and to investigate the possible interrelationships between the five thinking domains (teachers’ teaching philosophy, teaching objective, pedagogical content knowledge, teachers’ expectations and management style).